Skill formation in Japan and Southeast Asia (University of Tokyo Press, 1990)
Reported in an earlier version in the Japanese language in Jinzai keisei no kokusai kikaku: tonan Asia to Nihon (An international comparison of skill formation: Southeast Asia and Japan), Tokyo Keizai Shimposha, 1987.